Preparation and Study Of Zn(II) Complexes With Some Schiff Bases Derived From Acid Hydrazide-Benzil and Ethylenediamine - Ihsaan A. Mustafa; Zuhoor W. Al-Tuhafy (College of Education for Pure Sciences, 2012)
Abstract Some new macrocyclic and acyclic complexes having the general formula [ZnL]Cl2,[ZnLCl2],[Zn2LCl4] where L=Schiff base ligands derived from ethylene diamine with esters (diethylmalonate, diethylsuccinate and diethylphthalate) and benzil, where prepared by the reaction of zinc (II) chloride with ligands in ethanolic solution.1:1,2:1,1:2 stoichiometry of zinc (II) to ligand. Elemental analysis, molar conductance, infrared and ultraviolet studies reveal that the ligands in these complexes behave as tetra and octadentate forming tetra and hexa coordinated zinc (II) complexes respectively.